2013
DOI: 10.1093/glycob/cwt007
|View full text |Cite
|
Sign up to set email alerts
|

Annotation and structural elucidation of bovine milk oligosaccharides and determination of novel fucosylated structures

Abstract: Bovine milk oligosaccharides (BMOs) are recognized by the dairy and food industries, as well as by infant formula manufacturers, as novel, high-potential bioactive food ingredients. Recent studies revealed that bovine milk contains complex oligosaccharides structurally related to those previously thought to be present in only human milk. These BMOs are microbiotic modulators involved in important biological activities, including preventing pathogen binding to the intestinal epithelium and serving as nutrients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
200
2
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 167 publications
(211 citation statements)
references
References 54 publications
5
200
2
2
Order By: Relevance
“…Milk from humans and nonhuman mammals contain an abundant, complex, and diverse assortment of glycans and oligosaccharides (Aldredge et al, 2013;Urashima, Saito, Nakamura, & Messer, 2001). Many of these have biological activity, influencing gut maturation (Kuntz, Kunz, & Rudloff, 2009), the immune system (Lane, O'Callaghan, Carrington, & Hickey, 2013;Rescigno & Sabatino, 2009), and the intestinal microbiota (LoCasio et al, 2007;Marcobal et al, 2010;Sela et al, 2011;Ward, Niñonuevo, Mills, Lebrilla, & German, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Milk from humans and nonhuman mammals contain an abundant, complex, and diverse assortment of glycans and oligosaccharides (Aldredge et al, 2013;Urashima, Saito, Nakamura, & Messer, 2001). Many of these have biological activity, influencing gut maturation (Kuntz, Kunz, & Rudloff, 2009), the immune system (Lane, O'Callaghan, Carrington, & Hickey, 2013;Rescigno & Sabatino, 2009), and the intestinal microbiota (LoCasio et al, 2007;Marcobal et al, 2010;Sela et al, 2011;Ward, Niñonuevo, Mills, Lebrilla, & German, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The separation method was already described in our previous publication (Aldredge et al, 2013). The dried samples were dissolved in 1 mL of water and diluted ten times, and 1 mL aliquots were injected.…”
Section: Oligosaccharide Profilingmentioning
confidence: 99%
See 1 more Smart Citation
“…Using this method, >200 HMO structures can be separated. More recently, oligosaccharides in bovine colostrum were investigated by Aldredge et al [102], who employing nano-liquid chromatography tandem mass spectrometry, identified five fucosylated oligosaccharides that were found to be in common with human milk. Nano-LC chip/TOF MS offers an orthogonal dimension of retention time and accurate mass, making it possible to separate isomeric HMOs, with and without sialic acids, in a single-chromatographic separation.…”
Section: Liquid Chromatographymentioning
confidence: 99%
“…The compounds were extracted and matched to a BMO library [13] using the reproducible retention times and the accurate masses of each compound. The relative abundance of BMOs was determined.…”
Section: Compositional Analysis By Q-tof/mass Spectrometrymentioning
confidence: 99%